Application of reusable PZT sensors for monitoring intial hydration of concrete - Lim, Parry Weixiong. (2009)
For concrete structures, compressive strength information is essential during the curing period to determine the optimal demolding time. To avoid any significant long term ill effects on the structures, nondestructive structural health monitoring methods such as Electro Mechanical Impedance (EMI) sensing technique, which uses lead zirconate titanate (PZT) sensors, are employed as a built in monitoring system for strength gain monitoring of early age concrete.